Transformasi Pembelajaran Sains di Era Pendidikan 5.0 melalui Virtual Reality (VR) Millea Lab: Meningkatkan Pemahaman Konsep Sains dan Literasi Teknologi bagi Siswa Digital Native - Ani Anjarwati; Ryzca Siti Qomariyah; Dinar Ayu Prameswari; Serly Nurul Laili; Pepilian Dwi Retno Wahyuningrum (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to develop and evaluate MilleaLab Virtual Reality (VR) learning media to support elementary science learning within the framework of Education 5.0. The product was designed using the ADDIE model and validated by both media and content experts, each achieving a feasibility score of 96.67%, surpassing the minimum threshold of 80%. The implementation involved 225 students from Grades IV and V across four elementary schools in East Java. Students learned science topics on green plants and the digestive system through immersive VR-based activities. Effectiveness was measured using pre-test and post-test scores, yielding an overall mean N-Gain of 0.50, which falls into the moderate category. Reflection data collected through a six-item Likert-scale questionnaire showed that more than 60% of students rated the learning experience as very good, while none rated it poor or very poor. These results indicate that MilleaLab VR enhances students’ conceptual understanding and provides positive learning experiences. However, the variation in N-Gain across schools highlights the importance of adequate device availability, internet stability, and teacher readiness to optimize VR integration. This study concludes that MilleaLab VR is feasible and moderately effective for transforming science learning in elementary schools, contributing to digital literacy development in the Education 5.0 era.